Wood molasses as a preservative for high moisture barley: 1. Preservation and digestibility in pig - Huhtanen, Pekka (Agricultural and Food Science, 1984)
Wood molasses from sulphate spent liquor was tested as a preservative for high moisture barley. In Exp. 1 wood molasses was applied at levels of 8 and 16 % of barley dry matter (DM). In Exp. 2 an application level of 12 % was compared with AIV II solution used at a level of 3 l/1000 kg. Barley was rolled before ensiling and water was added so that the moisture content was 55 % in Exp. 1 and 55—60 % in Exp. 2. Digestibility and nitrogen retention in growing pigs, liveweight 31—81 kg, were determined for dried barley, propionic acid treated barley and barleys ensiled with AIV II or wood molasses (12 % of barley DM). In Exp. 1 the application level of 8 % unneulralized wood molasses (pH 2) was sufficient to prevent deterioration during storage. The preservative effect was based mainly on the acidity provided by organic acids. With the higher level of application the lactic acid content was lower (P < 0.05). In Exp. 2barley ensiled with neutralized wood molasses had a higher (P < 0.01) lactic and acetic acid content and a lower pH value (P < 0.05) than barley ensiled with AIV II. Wood molasses decreased protein breakdown during the storage. The effect of DM content on fermentation and proteolysis was greater for AIV II ensiled barley. During the storage the sugar content increased because of starch hydrolysis. DM, organic matter (OM), NFE and starch digestibilities were lower on diets of barley ensiled with AIV II and wood molasses than on dried barley diet (P < 0.05). OM digestibilities for the diets were 82.2, 81.0 and 85.4 %, respectively. The digestibility of barley treated with propionic acid was slightly lower than that of dried barley. No differences were found in nitrogen retention.